Leveraging Gamified Human Resources Platforms to Enhance Learning and Development Outcomes among Banking Employees - Rivai, Yutiandry (First Ciera Publisher, 2025)
This study aims to examine how gamified HR platforms influence learning and development outcomes among banking employees. This study employs a qualitative research approach to gain an in-depth understanding of how gamified HR platforms influence learning and development outcomes among banking employees. A case study design will be used, focusing on one or more banking institutions that have implemented gamified HR platforms for training and development. Data will be analyzed using thematic analysis. The findings demonstrate that gamification significantly improves learning engagement, motivation, and knowledge retention. Features such as progress tracking, scenario-based simulations, and leaderboards contributed to more positive learning experiences compared to traditional e-learning. Gamified HR platforms can help modernize compliance training and skill development, making them more relevant and enjoyable. Future studies can build upon this work in conduct quantitative or mixed-methods research to measure the statistical impact of gamification on learning outcomes and job performance.